Within-brood body size and immunological differences in Blue Tit (Cyanistes caeruleus) nestlings relative to ectoparasitism - Jorge Garrido-Bautista; Antonio Soria; Cristina E. Trenzado; Amalia Pérez-Jiménez; Eliana Pintus; José Luis Ros-Santaella; Nicola Bernardo; Mar Comas; Stanislav Kolenčík; Gregorio Moreno-Rueda (Avian Research, 2022)
Several ectoparasites parasitise nestlings decreasing their body condition, growth and survival. To minimise any loss of fitness due to ectoparasites, birds have developed a wide variety of defence mechanisms, potentially including hatching asynchrony. According to the Tasty Chick Hypothesis (TCH), the cost of parasitism would be reduced if ectoparasites tend to eat on less immunocompetent nestlings, typically the last-hatched chick in asynchronously hatched broods, as they are in poor body condition. Two predictions of the TCH are that immune capacity is lower in smaller nestlings than in larger ones and that parasites should provoke a more negative effect on smaller nestlings. Here, we test these predictions in a population of Blue Tits (Cyanistes caeruleus) whose broods are parasitised by Hen Fleas (Ceratophyllus gallinae) and Blowflies (Protocalliphora azurea). We recorded the presence of both ectoparasites and analysed the immunocompetence (number of leucocytes per 10,000 erythrocytes and cutaneous immune response to phytohaemagglutinin) and body condition of smaller and larger nestlings within individual broods. The leucocyte count was higher in smaller nestlings than in larger ones, whereas the cutaneous immune response did not differ between smaller and larger nestlings. Smaller nestlings, but not larger nestlings, had lower body mass when fleas were present. Blowflies, by contrast, had no detectable negative effect on nestlings. Overall, our findings provide partial support to the TCH. Lower immune capacity in smaller nestlings than in larger ones was not supported, but Hen Fleas seemed to negatively impact on smaller nestlings more than on larger ones.